2019
DOI: 10.1159/000502012
|View full text |Cite
|
Sign up to set email alerts
|

Iron Regulation by Molidustat, a Daily Oral Hypoxia-Inducible Factor Prolyl Hydroxylase Inhibitor, in Patients with Chronic Kidney Disease

Abstract: <b><i>Background/Aims:</i></b> The current treatment for anemia associated with chronic kidney disease (CKD) includes the administration of erythropoiesis stimulating agents (ESAs) combined with iron supplementation. Molidustat, a hypoxia-inducible factor prolyl hydroxylase inhibitor, has potential to treat anemia associated with CKD through increased erythropoietin production and improved iron availability. Here, we report the effect of molidustat on iron metabolism. <b><i>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…A single-center, randomized, single-blind, placebo-controlled, group-comparison, dose-escalation 1 phase study demonstrated that oral administration of molidustat to healthy volunteers elicited a dose-dependent increase in endogenous EPO and that all doses of molidustat were well tolerated [124]. In three randomized, controlled, phase 2 studies, which are the part of the DIALOGUE (DaIly orAL treatment increasing endOGenoUs Erythropoietin) program, molidustat diminished transferrin saturation (TSAT), hepcidin, ferritin, and iron concentrations and increased total iron-binding capacity (TIBC) in treatment-naïve patients not on dialysis [125]. In these studies, the efficacy, safety, and tolerability of molidustat were compared with placebo or alternative ESA therapy in patients with anemia of CKD.…”
Section: New Strategies Of Anemia Treatmentmentioning
confidence: 99%
“…A single-center, randomized, single-blind, placebo-controlled, group-comparison, dose-escalation 1 phase study demonstrated that oral administration of molidustat to healthy volunteers elicited a dose-dependent increase in endogenous EPO and that all doses of molidustat were well tolerated [124]. In three randomized, controlled, phase 2 studies, which are the part of the DIALOGUE (DaIly orAL treatment increasing endOGenoUs Erythropoietin) program, molidustat diminished transferrin saturation (TSAT), hepcidin, ferritin, and iron concentrations and increased total iron-binding capacity (TIBC) in treatment-naïve patients not on dialysis [125]. In these studies, the efficacy, safety, and tolerability of molidustat were compared with placebo or alternative ESA therapy in patients with anemia of CKD.…”
Section: New Strategies Of Anemia Treatmentmentioning
confidence: 99%
“…Desidustat (ZYAN1) is an oral hypoxia-inducible factor prolyl hydroxylase inhibitor (HIF-PHI) that stimulates erythropoiesis. Another novel hypoxia-inducible factor prolyl hydroxylase inhibitor, Molidustat, has the potential to treat anemia of CKD by increasing erythropoietin production and improving iron availability particularly, in non-dialysis patients [141]. However, HIFs have roles in other biological pathways, including in the expression of vascular endothelial growth factor (VEGF), which is associated with retinal disease and cancer [142].…”
Section: Novel Therapies For the Treatment Of Anemia Of Ckdmentioning
confidence: 99%
“…Group 1 (G1) included patients who went ≥12 weeks without receiving rhEPO, while group 2 (G2) included patients with stable ESA treatment for ≥8 weeks. DIALOGUE studies on molidustat, conducted by Akizawa et al [17, 18], included 3 trials of 3 kinds of people and 2 extensive trials. DIALOGUE 1 (D1) included patients with nondialysis-dependent chronic kidney disease (NDD-CKD) who were not previously treated with ESAs.…”
Section: Resultsmentioning
confidence: 99%